Assessing readiness of health facilities for implementing a social health insurance programme in Khyber Pakhtunkhwa, Pakistan - Shifa Salman Habib; Kiran Sohail Azeemi; Waqas Hameed; Junaid Ur Rehman Siddiqui; Ali Hussaini; Yusra Fahim; Adil Haider; Sameen Siddiqi (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the readiness of empanelled health facilities, encompassing secondary and tertiary care hospitals under the SCP Programme, to effectively implement the benefits package. Method: A cross-sectional survey was conducted in 38 public and private hospitals providing services under the SCP Programme across 10 districts of KP. The study utilized a Health Facility Assessment tool adapted from WHO’s Service Availability Readiness Assessment and other frameworks. The readiness was measured across 8 domains including Infrastructure, Governance, Health Information System, Infection Control, Sehat Card desk services, Billing & Reimbursement, Clinical Services, and Clinical Support Services. Data was collected from October 2022 to February 2023. Results: Based on our assessment, tertiary hospitals generally demonstrated a higher level of readiness compared to secondary hospitals across various domains. Tertiary hospitals demonstrated better readiness for access and infrastructure (92%), governance and leadership (97%) and infection prevention (79%). Secondary hospitals showed lower readiness scores in areas like HMIS (65%), billing & reimbursements (75%), and infection control (64%). The tertiary facilities outperformed secondary ones in clinical and support services, including emergency rooms, intensive care, surgery, obstetrics, laboratory services, blood banks, radiology, and pharmaceutical services. The overall preparedness was significantly higher in urban, relative to rural, hospitals across most indicators. Conclusion: The study underscores the need for targeted capacity building in KP’s health facilities, particularly secondary and remote hospitals. These improvements are crucial for successful implementation and expansion of the SCP programme. Keywords: Health Facility Readiness, Social Health Insurance, Sehat Card Plus Programme, Khyber Pakhtunkhwa, Health Services Evaluation.